2019
DOI: 10.2478/acph-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of baicalein on a model of allergic rhinitis

Abstract: Allergic rhinitis (AR) is a common disease that causes severe inflammation and even disabilities. Previous studies have reported baicalein to have an anti-inflammatory effect. However, the pharmacological action of baicalein on anaphylaxis has not been clarified yet. This study assessed the in vivo protective effect of baicalein post-treatment in an ameliorating ovalbumin (OVA)-sensitized AR rat model. Baicalein attenuated histological alterations, aberrant tissue repair and inflammation after OVA-induced AR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…It has been used over the years to treat various diseases, including rheumatism, sinusitis, skin pruritus, and headaches (Figures 1(a) and 1(b) ) [ 18 ]. The Xanthii fructus has been shown to reduce mast cell-mediated allergy reactions [ 19 ], anti-inflammatory actions in lipopolysaccharide-stimulated inflammatory responses [ 20 ], and prevention of β -cell damage in type 1 diabetes [ 21 ].…”
Section: Xanthium Fructusmentioning
confidence: 99%
“…It has been used over the years to treat various diseases, including rheumatism, sinusitis, skin pruritus, and headaches (Figures 1(a) and 1(b) ) [ 18 ]. The Xanthii fructus has been shown to reduce mast cell-mediated allergy reactions [ 19 ], anti-inflammatory actions in lipopolysaccharide-stimulated inflammatory responses [ 20 ], and prevention of β -cell damage in type 1 diabetes [ 21 ].…”
Section: Xanthium Fructusmentioning
confidence: 99%
“…On day 31 of the study, all rats were placed into a separate cage and observed for 30 min after the final OVA challenge. 18,19 The numbers of sneezing and rubbing episodes were recorded.…”
Section: Evaluation Of Nasal Symptommentioning
confidence: 99%
“…These studies have been preceded by several in vitro tests in which cell lines were used [8]. Natural hydroxyflavones have a range of biological activities, including anticancer [9], antioxidative [10], anti-inflammatory [11] antiallergic [12], hepatoprotective [13] and neuroprotective ones [14]. They prevent diabetes mellitus complications, such as retinopathy, which may lead to blindness [15].…”
Section: Introductionmentioning
confidence: 99%